Co-operation over Distance? The Spatial Dimension of Inter-organisational Innovation Collaboration - Anja Dettmann; Sidonia von Proff; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2012)
In the literature there is a controversy about the relevance of the spatial dimension in innovation collaboration. We examine the link between the spatial composition of group members and group characteristics which are important for performing innovation projects. To this end, we introduce a social-psychological approach to the field of economic geography. The empirical part is a longitudinal study of 49 inter-organisational innovation groups in Germany. We find that the share of regional partners is rather stable after a funded formation stage. Hence, policy measures aiming at inter-regional collaboration have to be employed at an early stage of group development.
Keywords: L14; R12; O38; 330; innovation collaboration; collaboration over distance; network formation; Germany